Effectiveness of dry needling for chronic nonspecific neck pain: a randomized, single-blinded, clinical trial. Issue 9 (September 2016) - Cerezo-Téllez, Ester; Torres-Lacomba, María; Fuentes-Gallardo, Isabel; Perez-Muñoz, Milagros; Mayoral-del-Moral, Orlando; Lluch-Girbés, Enrique; Prieto-Valiente, Luis; Falla, Deborah
Abstract : Abstract: Chronic neck pain attributed to a myofascial pain syndrome is characterized by the presence of muscle contractures referred to as myofascial trigger points. In this randomized, parallel-group, blinded, controlled clinical trial, we examined the effectiveness of deep dry needling (DDN) of myofascial trigger points in people with chronic nonspecific neck pain. The study was conducted at a public Primary Health Care Centre in Madrid, Spain, from January 2010 to December 2014. A total of 130 participants with nonspecific neck pain presenting with active myofascial trigger points in their cervical muscles were included. These participants were randomly allocated to receive: DDN plus stretching (n = 65) or stretching only (control group [n = 65]). Four sessions of treatment were applied over 2 weeks with a 6-month follow-up after treatment. Pain intensity, mechanical hyperalgesia, neck active range of motion, neck muscle strength, and perceived neck disability were measured at baseline, after 2 sessions of intervention, after the intervention period, and 15, 30, 90, and 180 days after the intervention. Significant and clinically relevant differences were found in favour of dry needling in all the outcomes (all P < 0.001) at both short and long follow-ups. Deep dry needling and passive stretching is more effective than passive stretching alone in people with nonspecific neck pain. The results support the use of DDN in the management of myofascial pain syndrome in people with chronic nonspecific neck pain. Abstract : Deep dry needling of myofascial trigger points is an effective treatment for patients with chronic nonspecific neck pain.